Combination of Hydroponic Natural Nutrient Solution Effect on Kale Plant Growth (Ipomoea reptans) Using Wick System - Al Toriq, Muhammad Rizki; Puspitawati, Rinie Pratiwi; Oxi, Rizki Yulia (LenteraBio : Berkala Ilmiah Biologi, 2025)
Synthetic AB mix nutrients pose long-term risks. Thus, it is necessary to discover alternatives, such as natural and environmentally friendly nutrient solutions. The combination of several ingredients will create a perfect nutrient solution formula for kale growth. The purpose of this study was to determine the combination of natural nutrient solutions effect and to determine the best natural nutrient combination formula for kale growth. Experimental research used a completely randomized design (CRD) with eight treatments and three repetitions. The treatment consisted of control, namely the use of synthetic AB mix nutrition and manipulation treatment using a combination of catfish waste water extract, rice washing water, banana peels, onion peels, aloe vera and bean sprouts. Data was tested quantitatively using the Anova test and Duncan's test at 5% level. The results showed that the combination of natural nutrient solutions had a significant effect on the growth of kale. Formal A produces the best formula with the composition of ingredients water (500 ml) + catfish wastewater (500 ml) + aloe vera soak (10 ml) + bean sprouts soak (10 ml). Formula A generated an average plant height of 42.7 cm in the long category, 15 leaves in the ‘numerous’ category, a stem diameter of 1.01 cm in the large category, a root length of 13.3 cm in the long category, and a plant wet weight of 10 g in the heavy category.